Strategic Planning in the Middle Byzantine Period: A "Limitrophe" Policy Reintroduced? - Gjalevski, Dragan (Studia Ceranea, 2023)
In order to maintain or improve its political stability and overall might every state conducts certain policies, both domestic and foreign, throughout its history. They are usually a result of a systematic planning, encompassing in the process multiple state sectors. The Byzantine Empire was no exception. Throughout centuries of existence, the imperial government implemented numerous reforms and carried out reorganisation in the military, administrative and fiscal departments, with the intention to improve its governance. Creation of the military commands – strategides, thémata and tágmata corps are only some of the changes, and their implementation certainly required prior planning in accordance with the requirements and capacity of the state. In relation to foreign policy, starting from the mid-ninth century, a formation of a number of client states that were more or less politically dependent on Constantinople can be observed on the Byzantine borders; their existence ended around the mid-eleventh century. This paper aims to examine the process of establishing client states on the Byzantine borders, i.e., whether it was a policy initiated and subsequently applied by the imperial government as a result of some pre-determined planning, or whether it was just an ad hoc solution. This paper was presented on the 24th International Congress of Byzantine Studies, Venice and Padua, 22-27 August 2022.